COVID-19 and informal work: Degrees and pathways of impact in 11 cities around the world - Martha Alter Chen; Erofili Grapsa; Ghida Ismail; Sarah Orleans Reed; Michael Rogan; Marcela Valdivia (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper presents findings from two rounds (2020 and 2021) of a study on the impact of the COVID-19 crisis on informal workers in 11 cities across five regions of the world (Africa, Asia, Eastern Europe, Latin America, and North America). The study, carried out by the WIEGO network in partnership with local organizations of informal workers in each city, included a survey questionnaire and key informant interviews, both conducted by phone. The study findings confirm that the pandemic recession severely undermined the livelihoods of informal workers with limited recovery by mid-2021. The study also examined the degree-and pathways-of impact between, and within, different sectors of informal workers and provides insights and demands from informal workers in their own words.
Keywords: C83; J01; J46; 330; informal economy; impact of COVID-19 pandemic recession; work; earnings; food security; coping strategies